Strategic alliances between the Czech SMEs and its impact on competitiveness - Hromadka, Martin; Tyll, Ladislav; Srivastava, Mohit; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2018)
The thesis assesses the use of strategic alliances by small and medium enterprises in the Czech Republic as a strategic business tool. It reviews the available literature on the topic and provides an analytical framework to be used in the analysis of the propensity of SMEs to engage in strategic alliances, the types of strategic alliances these engage in and in the analysis of its impact on their competitiveness. The researcher engages in the review of publicly available sources and in a survey of the SMEs’ representatives to gather data. Quantitative evaluation of the main study questions and hypotheses based on the survey was undergone and the positive impact of the alliances on the increased competitiveness and on the international business was not proved and hypotheses were rejected. Nonetheless, there is an evidence of the impact of some type of strategic alliances on the SMEs’ competitiveness. The effects of strategic alliances should be further analyzed to prove/disprove the results and find the reasons for the limited impact on the competitiveness.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses